Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1186/s12913-023-09185-1
|View full text |Cite
|
Sign up to set email alerts
|

Legitimizing neglect - a qualitative study among nursing home staff in Norway

Abstract: Introduction Residents in nursing homes do not always get qualitatively good nursing care, and research shows that residents’ basic care needs are sometimes neglected. Neglect in nursing homes is a challenging and complex issue, yet a preventable one. Nursing home staff are at the frontline of detecting and preventing neglect but may also be the ones causing it. It is essential to understand why and how neglect happens in order to recognize, expose, and prevent its occurrence. Our aim was to ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…The pattern of the included papers suggested that the scientific literature describing fundamental nursing (Q1), the experience and descriptions of fundamental nursing (Q2), interventions or activities targeting fundamental nursing and continuity of care (Q3) were in most cases focusing on individual physical needs. In many papers, fundamental nursing was described to point towards fragmented and suboptimal fundamental nursing in home- and facility-based care, in line with previous literature reviews [ 10 , 114 116 ] and primary research studies [ 117 , 118 ]. The pattern of fragmented care could also be put in relation to one of the recurring descriptions from the analysis, that is, the lack of both sufficient and adequately trained nursing personnel and relationship to less-than-optimal fundamental nursing within home- and facility-based care [ 68 *, 69 *, 71 *, 72 *, 73 *, 75 *, 79 *, 80 *, 83 *, 89 *, 90 *, 93 *, 94 *, 97 *, 98 *, 107 *].…”
Section: Discussionmentioning
confidence: 73%
“…The pattern of the included papers suggested that the scientific literature describing fundamental nursing (Q1), the experience and descriptions of fundamental nursing (Q2), interventions or activities targeting fundamental nursing and continuity of care (Q3) were in most cases focusing on individual physical needs. In many papers, fundamental nursing was described to point towards fragmented and suboptimal fundamental nursing in home- and facility-based care, in line with previous literature reviews [ 10 , 114 116 ] and primary research studies [ 117 , 118 ]. The pattern of fragmented care could also be put in relation to one of the recurring descriptions from the analysis, that is, the lack of both sufficient and adequately trained nursing personnel and relationship to less-than-optimal fundamental nursing within home- and facility-based care [ 68 *, 69 *, 71 *, 72 *, 73 *, 75 *, 79 *, 80 *, 83 *, 89 *, 90 *, 93 *, 94 *, 97 *, 98 *, 107 *].…”
Section: Discussionmentioning
confidence: 73%
“…Intentional or not, this handling of cognitive dissonance and moral distress, depicts neglectful behaviour as less severe, and thus easier for the staff to face in their everyday work. This is also indicated by previous research showing that nursing staff regularly fail to recognise their own practices as neglectful, normalising missed care as a way of legitimising neglect [ 45 ]. Tolerating neglect may be a way of enabling existing and insufficient care practices.…”
Section: Discussionmentioning
confidence: 88%
“…The sample included 13 registered nurses (RN), 12 licensed practical nurses (LNP), one social worker (SW), one social educator (SE) and three nurse assistants (A). A more detailed overview of participants has been given elsewhere [ 45 ].…”
Section: Methodsmentioning
confidence: 99%
“…The recent theoretical academic literature shows that healthcare professionals are particularly susceptible to burnout due to risky decision-making involving people, empathy, and responsibility (Lluch et al 2022). The literature addressing burnout among nurses in retirement homes, where specialised services are tailored to individuals typically aged 80 and above (Friganović et al 2019;Lund et al 2023), is noticeably sparse, especially when juxtaposed with the extensive research conducted on various aspects of nursing practice (De Diego-Cordero et al 2022) and investigations into COVID-19 prevalence rates (Mary Pappiya et al 2023), but not on demographic issues (Sherman and Touhy 2017). Consequently, there is an imperative to establish conducive conditions for nursing staff to flourish and grow, ensuring their capacity to provide high-quality care.…”
Section: Introductionmentioning
confidence: 99%